2001
DOI: 10.1192/bjp.178.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter lesions in bipolar affective disorder: relationship to outcome

Abstract: Subcortical white matter lesions are associated with poor outcome bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 24 publications
4
83
2
1
Order By: Relevance
“…Studies examining white matter lesions in non-diabetic, asymptomatic volunteers aged 20 to 83 years found that 11 to 73% of participants had white matter hyperintensities ranging from grade 1 to grade 3 [29][30][31][32][33][34] with more white matter hyperintensities occurring among older participants [29,32]; for those under 50 years of age, 11 to 42% of participants had either deep white matter or periventricular hyperintensities [29,31,33,34]. This prevalence of white matter hyperintensities in non-diabetic controls suggests that some white matter hyperintensities, particularly grades 1 and 2, may not be clinically significant and emphasises the importance of including a non-diabetic control group when assessing the effect of diabetes on brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining white matter lesions in non-diabetic, asymptomatic volunteers aged 20 to 83 years found that 11 to 73% of participants had white matter hyperintensities ranging from grade 1 to grade 3 [29][30][31][32][33][34] with more white matter hyperintensities occurring among older participants [29,32]; for those under 50 years of age, 11 to 42% of participants had either deep white matter or periventricular hyperintensities [29,31,33,34]. This prevalence of white matter hyperintensities in non-diabetic controls suggests that some white matter hyperintensities, particularly grades 1 and 2, may not be clinically significant and emphasises the importance of including a non-diabetic control group when assessing the effect of diabetes on brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…Periventricular lesions have been reported, but deep WMH occur most frequently (Ahn et al, 2004;Moore et al, 2001;Silverstone et al, 2003). Interestingly, no studies report the most severe grades on the scales for assessing these lesions, which were developed to rate demyelinating disease, indicating that these white matter changes are subtle.…”
Section: White Mattermentioning
confidence: 99%
“…Neuroimaging research in BD has already produced several data documenting the involvement of different cortical and subcortical regions in different phases of the illness. In particular, published studies explored structural and functional abnormalities present in BD and tried to establish specific correlations with outcome (Moore et al, 2001;Wingo et al, 2009) as well as difficult-to-treat conditions such as treatment resistant forms (Regenold et al, 2008). The possibility to study cognitive function in BD through fMRI represents another major acquisition of neuroimaging in psychiatric research.…”
Section: Discussionmentioning
confidence: 99%